PENDAMPINGAN MASYARAKAT DALAM UPAYA MENANGKAL RADIKALISME DAN TERORISME DI MASJID AL-JAMA’AH KOMPLEK BIMA ESTATE KOTA CIREBON - Saumantri, Theguh (ABDI MAKARTI, 2024)
The increased threat of radicalism and terrorism in Indonesia demands a holistic and sustainable response from various sectors of society. In this regard, community engagement activities at Masjid Al-Jama’ah Complex, Bima Estate, Cirebon City aim to enhance understanding and active involvement of the community in combating radicalism and terrorism. Participatory Action Research (PAR) is employed as the method in conducting this community engagement. This method is considered transformative as it aims to empower and bring about significant changes within the community. The conclusion drawn from this activity is that community mentoring in combating radicalism and terrorism at Masjid Al-Jama’ah Complex, Bima Estate, Cirebon City is a strategic and relevant step in addressing the challenges of religious extremism. Through inclusive and proactive approaches, this activity is expected to enhance community understanding of the dangers of radicalism and terrorism, and promote moderate and tolerant religious practices.